Technics and Contingency - Alan Díaz Alva (Media Theory)
This text aims to explore the relationship between technics and contingency within a context where computational technologies often have the effect of domesticating the latter, leading to its statistical reduction within the realm of the probable. I will argue that the post-prosthetic and non-correlational character of these technologies prompts us to pursue a line of inquiry that calls for a different understanding of contingency. Instead of solely assigning it to domains external to computational technologies (the ‘externality thesis’), this perspective identifies a form of contingency inherent in these technologies themselves (the ‘internality thesis’). I will develop this approach through a comparative analysis of the work of M. Beatrice Fazi and Mark B.N. Hansen, authors who both draw from Alfred N. Whitehead’s process ontology. I will underscore the tensions between their proposals, trying to identify the main divergences within their speculative ontologies of computation. However, I will also propose that we can read them as complementary propositions that account for the ontological productivity of computational media and operations, allowing us to theorise a form of computational contingency independent from the tendencies towards algorithmic closure and determinism present in contemporary technical systems.